Beyond daily dosing: clinical experience. - Cooper, C (2006)
Osteoporosis has had a significant public health impact, with many sufferers experiencing fractures. Such fractures lead to increased disability, mortality and reduced quality of life, all of which raise healthcare costs. Oral bisphosphonates are associated with significant antifracture efficacy and have therefore become the mainstay of treatment for postmenopausal osteoporosis. Poor therapeutic adherence with daily bisphosphonates has been improved by the introduction of weekly regimens, although adherence levels remain suboptimal. Bisphosphonate regimens with dosing intervals beyond a week have therefore been developed to address this issue. Oral ibandronate, a potent nitrogen-containing bisphosphonate, has been studied using daily and intermittent regimens (between-dose interval >2 months). The initial phase II 2-year study confirmed the feasibility of the intermittent regimen, providing increases in lumbar spine bone mineral density (BMD) superior to placebo (P < 0.01) and equivalent to the daily regimen (5.64% vs. 5.54%, respectively). BONE (Oral iBandronate Osteoporosis vertebral fracture trial in North America and Europe), a large phase III 3-year study was subsequently initiated, including 2946 women with postmenopausal osteoporosis and testing both a daily as well as an intermittent regimen with a dose-free interval of more than 2 months. Significant vertebral antifracture efficacy (the primary study endpoint) was demonstrated with daily (2.5 mg) and intermittent (20 mg every other day for 12 doses every 3 months) ibandronate in comparison with placebo (P < or = 0.0006). As a result of the study not being designed and powered to show an effect on non-vertebral fractures and the overall population being at low risk for osteoporotic fractures, differences in the incidence of non-vertebral fractures were similar between groups (8.2-9.1%) However, a post hoc analysis in a subgroup of patients with a femoral neck BMD T-score < -3.0 showed that daily ibandronate significantly reduced the risk of non-vertebral fractures (P = 0.012). Both regimens were associated with significant increases in lumbar spine and proximal femur BMD and normalization of bone turnover. As determined by adverse event incidence and laboratory evaluation, the safety profile for both ibandronate regimens was similar to that observed for placebo. The BONE study therefore confirmed that daily or intermittent ibandronate is an effective and well-tolerated treatment for postmenopausal women. Being the first study to demonstrate antifracture efficacy with an intermittent regimen, it provided "proof of concept" for beyond weekly dosing with ibandronate and prompted further development of a more convenient once-monthly regimen.